Human keratinocyte induction of rapid effector function in antigen-specific memory CD4+ and CD8+ T cells. - Black, A; Ardern-Jones, MR; Kasprowicz, V; Bowness, P; Jones, L; Bailey, A; Ogg, G (2007)
The ability of human keratinocytes to present antigen to T cells is controversial and, indeed, it has been suggested that keratinocytes may promote T cell hyporesponsiveness. Furthermore, it is unclear whether keratinocytes can process antigen prior to MHC class I and class II presentation. We tested the ability of keratinocytes to induce functional responses in epitope-specific CD4+ and CD8+ memory T cells using peptides, protein and recombinant expression vectors as sources of antigen. Keratinocytes were able to efficiently process and present protein antigen to CD4+ T cells, resulting in cytokine secretion (Th1 and Th2). This interaction was dependent on keratinocyte expression of HLA class II and ICAM-1, which could be induced by IFN-gamma. In addition, keratinocytes could present virally encoded or exogenous peptide to CD8+ T cells, resulting in T cell cytokine production and target cell lysis. Finally, T cell lines grown using keratinocytes as stimulators showed no loss of function. These findings demonstrate that keratinocytes are able to efficiently process and present antigen to CD4+ and CD8+ memory T cells and induce functional responses. The findings have broad implications for the pathogenesis of cutaneous disease and for transcutaneous drug or vaccine delivery.